Pharmacokinetics of Galantamine, a Cholinesterase Inhibitor, in Several Animal Species - Monbaliu, Johan; Verhaeghe, Tom; Willems, Bart; Bode, Wilhelmina; Lavrijsen, Karel; Meuldermans, Willem (Arzneimittelforschung, 2003)
In this publication, single and repeated dose experiments in rats, mice, rabbits and dogs are reported to assess the pharmacokinetics of galantamine (CAS-1953-04-4), a tertiary alkaloid with reversible cholinesterase inhibiting and nicotinic receptor modulatory properties developed for the treatment of Alzheimer’s disease in humans.Rats received single i.v. and single and repeated oral administrations of various doses, up to 160 mg/kg/day. In mice, only repeated oral administration of galantamine was investigated, up to 40 mg/ kg/day. Galantamine single and repeated oral doses up to 32 mg/kg/day were administered to female pregnant rabbits. Beagle dogs received single i.v. and single and repeated oral administrations of doses up to 8 mg/kg/day.Generally, oral absorption was rapid, with maximal plasma levels reached within 2 h in all species. Absolute oral bioavailability of a gavage dose was high in rat (77 %) and dog (78 %). In mice and rats, the bioavailability of galantamine administered via the food was lower than of galantamine administered by gavage. Elimination half-life of galantamine was relatively large in rat and dog and smaller in mouse and rabbit. In general, galantamine displayed dose-proportional to somewhat more than dose-proportional kinetics. In rats, plasma levels were lower in females than in males, whereas in mice, females showed higher levels than males. No gender differences were observed in dogs. No relevant differences in exposure to galantamine were found in rats and dogs upon oral administration of galantamine obtained as a natural extract or from chemical synthesis.The exposure to the active metabolite norgalantamine in plasma of the different animal species was low, except in the dog where the steady-state norgalantamine exposure was approximately 75 % of galantamine exposure.Galantamine plasma levels after single and repeated administration of 10 mg/kg/day in all species investigated except female rat and rabbit were much higher than mean therapeutic plasma levels of galantamine obtained in humans. The pharmacokinetic profile of galantamine after repeated oral administration in rats was most similar to the profile obtained after repeated administration of 12 mg b.i.d. in man.
Keywords: Alzheimer’s disease; CAS 1953-04-4; Cholinesterase inhibitor; Galantamine, absorption, animal pharmacokinetics, bioavailability; Reminyl®